REINTEPRETASI AYAT-AYAT AHKAM TENTANG ZAKAT (Analisa Terhadap Qs. Al-Baqarah 110, Qs. al-taubah 60 & Qs. al-An'am 141) - Abdul Basid; Nur Faizin (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2021)
Abstract: This paper seeks to analyze the ahkam verses in al-Qur'an Al-Baqarah verse 110, al-taubah verse 60 and al-An'am verse 141. Interpretive analysis is carried out based on several books of ahkam's interpretation, such as Tafsir Munir. Wahbah al-Zuhaili, al-Jami 'li Ahkam al-Qur'an by al-Qurthubi, Al-Tabari, Tafsir Ayat al-Ahkam by al-Jashshash, Teungku Muhammad Hasbi al-Shidiqi, Muhammad Quraish Shihab, Yusuf al-Qardhawi , and many more. By using a content analysis approach to Al-Baqarah verse 110, al-taubah verse 60 and al-An'am verse 141, it is found that: Allah in al-Qur'an found 15 verses coupled with zakat with prayer. Prayer improves the situation of the individual while zakat improves the condition of society, and both are factors of happiness in the world and the hereafter. Allah commands zakat because this obligation can strengthen the relationship between rich people and poor people, so that a close unity is created between them and they become one whole body (society, nation). Keywords: verse ahkam; zakat; analysis of interpretation; al-Baqarah; al-taubah Abstrak: Tulisan ini berusaha mengupas ayat-ayat ahkam dalam al-Qur’an Al-Baqarah ayat 110, al-taubah ayat 60 dan al-An'am ayat 141. Analisis penafsiran dilakukan berdasarkan pada beberapa kitab tafsir ahkam, seperti Tafsir Munir karya Wahbah al-Zuhaili, al-Jami’ li Ahkam al-Qur’an karya al-Qurthubi, Al-Thabari, Tafsir Ayat al-Ahkam karya al-Jashshash, Teungku Muhammad Hasbi al-Shidiqi, Muhammad Quraish Shihab, Yusuf al-Qardhawi, dan masih banyak lagi. Dengan menggunakan pendekatan analisis isi (content analysis) terhadap Al-Baqarah ayat 110, al-taubah ayat 60 dan al-An'am ayat 141, didapati temuan bahwa: Allah dalama al-Qur’an ditemukan 15 ayat menggandeng zakat dengan shalat. Shalat memperbaiki keadaan individu sedangkan zakat memperbaiki keadaan masyarakat, dan keduanya menjadi faktor-faktor kebahagiaan dunia dan akhirat. Allah memerintahkan zakat karena kewajiban tersebut dapat mengukuhkan hubungan orang-orang kaya dengan orang-orang miskin, sehingga terwujudlah persatuan yang erat antar mereka dan jadilah mereka satu tubuh (masyarakat, bangsa) yang utuh. Kata kunci: ayat ahkam;zakat;analisis tafsir; al-Baqarah; al-taubah